2013
DOI: 10.1021/ac4016787
|View full text |Cite
|
Sign up to set email alerts
|

Pseudotargeted Metabolomics Method and Its Application in Serum Biomarker Discovery for Hepatocellular Carcinoma Based on Ultra High-Performance Liquid Chromatography/Triple Quadrupole Mass Spectrometry

Abstract: Untargeted analysis performed using full-scan mass spectrometry (MS) coupled with liquid chromatography (LC) is commonly used in metabolomics. Although they are commonly employed, full-scan MS methods such as quadrupole-time-of-flight (Q-TOF) MS have been restricted by various factors including their limited linear range and complicated data processing. LC coupled with triple quadrupole (QQQ) MS operated in the multiple reaction monitoring (MRM) mode is the gold standard for metabolite quantification; however,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
141
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 193 publications
(149 citation statements)
references
References 36 publications
6
141
1
1
Order By: Relevance
“…This improved performance results primarily from the fact that GOT-MS is based on the QQQ-MS platform, which was also observed in previous studies. 35,36 In addition, while our Q-TOF generally has good reproducibility for strong signals, these signals cannot be too large, because signal saturation will deteriorate mass accuracy (as well as linearity). Therefore, the advantages of high resolution and high mass accuracy can be compromised in traditional global profiling.…”
Section: Discussionmentioning
confidence: 99%
“…This improved performance results primarily from the fact that GOT-MS is based on the QQQ-MS platform, which was also observed in previous studies. 35,36 In addition, while our Q-TOF generally has good reproducibility for strong signals, these signals cannot be too large, because signal saturation will deteriorate mass accuracy (as well as linearity). Therefore, the advantages of high resolution and high mass accuracy can be compromised in traditional global profiling.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, UPLC-QTOF/MS and UPLC-MS/MS approaches were used for qualitative and quantitative analyses of serum biomarkers for patients with HCC. The results indicated that patients with HCC had decreased LPCs, increased long-chain and decreased medium-chain acylcarnitines, and increased aromatic and decreased branched-chain amino acid [30]. UPLC-QTOF/MS and UPLC triple quadrupole linear ion trap MS approaches were performed on qualitative and quantitative comparisons of metabolite levels in sera of HCC patients and cirrhosis patients from Egypt [31].…”
Section: Hepatocarcinoma (Hcc) Liver Cirrhosis and Chronic Liver Dismentioning
confidence: 99%
“…Therefore, an unbiased and robust discrimination method should be developed to enhance the efficiency of analytical processes in xenobiotic metabolism research. By measuring and mathematically modelling changes in the levels of products of metabolism found in biological fluids and tissues [10][11][12], untargeted metabolomics provides fresh insight into subtle changes of endogenous components [13][14][15], and also could be extended to xenobiotics and related metabolites to which we are exposed. Applying untargeted metabolomicsdriven approach, the interesting variables could be extracted easily from the xenobiotic metabolome without the need for priori knowledge of the compound structure.…”
mentioning
confidence: 99%